2009
DOI: 10.1007/s00418-009-0627-8
|View full text |Cite
|
Sign up to set email alerts
|

DEHP effects on retinal vessels in newborn rats: a qualitative and quantitative analysis

Abstract: Di-(2-ethylhexyl)-phthalate (DEHP), employed in polyvinyl chloride fabrication and released by endotracheal tubes, is known to cause alterations to several mammalian tissues, markedly in immature animals. The high incidence and severity of bronchopulmonary dysplasia and retinopathy in preterm babies submitted to endotracheal intubation prompted us to investigate the effects of DEHP in lung and retina perinatal development. We previously demonstrated that in rats delivered and breast-fed by DEHP-treated mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In addition, Federica Romani indicated that levels of VEGF protein in human luteal cells had a statistically significant decrease after incubation with DEHP [ 19 ]. Moreover, DEHP treatment negatively affects the development of retinal vessels in newborn rats [ 27 ]. These data suggest that DEHP negatively influences corpus luteum function by inhibiting luteal angiogenesis in pregnant mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Federica Romani indicated that levels of VEGF protein in human luteal cells had a statistically significant decrease after incubation with DEHP [ 19 ]. Moreover, DEHP treatment negatively affects the development of retinal vessels in newborn rats [ 27 ]. These data suggest that DEHP negatively influences corpus luteum function by inhibiting luteal angiogenesis in pregnant mice.…”
Section: Discussionmentioning
confidence: 99%
“…Zei et al . observed retinal vessel remodelling in immature rat pups subjected to DEHP, and made a link with the high incidence of retinopathy of prematurity in ventilated premature infants . Finally, concerns are emerging regarding the potential neurodevelopmental consequences of early phthalate exposure in preterm neonates, as different neurobehavioural changes were observed following exposure in human fetuses at the same critical developmental window .…”
Section: Resultsmentioning
confidence: 95%
“…The authors clearly demonstrated that in DEHPtreated newborns the alveolarization process is dramatically altered. In another study, Zei et al (2009) studied DEHP eVects on retinal vessels in newborn rats. Extensive vascular remodeling after DEHP exposure again pointed to the severe and pathogenic eVects of DEHP during perinatal development of various tissues.…”
Section: Infectious Diseasesmentioning
confidence: 98%